PENINGKATAN PENGETAHUAN DAN SELF-EFFICACY UPAYA PENCEGAHAN COVID-19 MELALUI EDUKASI GIZI KONVENSIONAL Increased Knowledge and Self-Eﬃcacy of COVID-19 Prevention through Conventional Nutrition Education - Qonita Rachmah; Triska Susila Nindya; Arif Sabta Aji; Nabilla Rachmah; Nabiil Ikbaar Maulana; Asri Meidyah Agustin; Junaida Astina; Sitti Patimah (Universitas Airlangga, 2021)
The COVID-19 pandemic has impact on various sectors, especially in the health sector. Eﬀorts to prevent COVID- 19 can be done through the application of health protocols and balanced nutrition intake. There were a lot of misinformations related to COVID-19 prevention that might be a risk of increasing positive rate cases. The aim of this study was to determine the eﬀectiveness of conventional nutrition education on knowledge and self-eﬃcacy of COVID-19 prevention eﬀorts. Study subjects of this study were 23 adults aged 19-65 years and taken by total sampling method. Nutritional knowledge data were collected using a questionnaire containing ten questions, while self-eﬃcacy was assessed by creating a structured questionnaire on a scale of 0-100. Conventional education was given in the form of lectures related to the role of balanced nutrition, hoaxes related to food to prevent or treat COVID-19, and other COVID-19 prevention eﬀorts for 90 minutes. Before and after education data were analyzed using paired t-test with SPSS version 23. This study results showed that nutrition education significantly improves nutritional knowledge (mean score before and after = 69.6 + 10.2 and 85.7 + 10.4; p < 0.001), self-eﬃcacy to apply a balanced nutrition pattern (mean scores before and after = 68.2 + 13.0 and 75.5 + 17.5; p = 0.014), and the self-eﬃcacy of implementing the health protocol (mean score before and after = 82.3 + 7.8 and 87.0 + 6.8; p = 0.002). This research can be used as a benchmark for the importance of expanding the coverage of conventional nutrition education to the wider community.